2016
DOI: 10.1007/s00394-016-1155-7
|View full text |Cite
|
Sign up to set email alerts
|

A review of iron studies in overweight and obese children and adolescents: a double burden in the young?

Abstract: A higher prevalence of ID, or risk of ID, among OW and OB children and adolescents has been consistently observed. Chronic inflammation caused by excessive adiposity offers a plausible explanation for this finding, rather than dietary factors. However, future studies must employ screening for the presence of both acute and chronic infections and inflammatory conditions and report other factors such as pubertal status. Intervention studies, although few, indicate that OW and OB children and adolescents have red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 97 publications
5
43
0
6
Order By: Relevance
“…Obese individuals despite their excessive dietary and caloric intake have an unbalanced diet based on carbohydrates and fats [35]. This has also been confirmed for overweight and obese children by Hutchinson [36]. This systematic review concluded that overweight and obese children and adolescents have a higher prevalence or risk of ID, and the evidence is consistent.…”
Section: Id Ida Poverty and Obesitysupporting
confidence: 62%
See 1 more Smart Citation
“…Obese individuals despite their excessive dietary and caloric intake have an unbalanced diet based on carbohydrates and fats [35]. This has also been confirmed for overweight and obese children by Hutchinson [36]. This systematic review concluded that overweight and obese children and adolescents have a higher prevalence or risk of ID, and the evidence is consistent.…”
Section: Id Ida Poverty and Obesitysupporting
confidence: 62%
“…This systematic review concluded that overweight and obese children and adolescents have a higher prevalence or risk of ID, and the evidence is consistent. However, Hutchinson [36] emphasized that the true relationship between body fat mass and iron absorption is still to be clarified. Low-hemoglobin level was found among overweight/obese pregnant women [19].…”
Section: Id Ida Poverty and Obesitymentioning
confidence: 99%
“…It has been documented that OW-OB are emerging risk factors for ID given their pro-inflammatory role in promoting increased hepcidin synthesis and restricted iron export activity in cells. 7,19,20 While ID resulting from an inflammatory process (commonly promoted by OB) can lead to anemia of inflammation, cross-sectional studies of Mexican children have consistently demonstrated that a high BMI is inversely associated with anemia. 3,21 García and colleagues found no association between low-iron status and OW/OB in a sample of Mexican children.…”
Section: Discussionmentioning
confidence: 99%
“…Asimismo estudios de intervención muestran que en los niños obesos ané-micos la respuesta a la suplementación del hierro por vía oral se ha visto reducida (37) . Este detalle habría que tomarlo en cuenta, ya que dar sulfato ferroso es obligatorio en los niños menores de 5 años.…”
Section: Discussionunclassified